Freestanding μm-thin nanomesh electrodes exceeding 100x current density enhancement for high-throughput electrochemical applications. (December 2022) - Plankensteiner, Nina; Rupp, Rico; Steegstra, Patrick; Singh, Sukhvinder; Canto, Jorge Giribet; Wodarz, Siggi; Blom, Martijn J.W.; John, Joachim; Mees, Maarten; Vereecken, Philippe M.
Abstract: Nanomeshes (NMs), regularly interconnected 3D nanowire-networks, obtained from electroplating in rationally designed alumina templates, are attractive for numerous fields due to their extremely high surface area and porosity. Until now, non-porous support substrates were required to provide sufficient mechanical robustness to the highly porous NM. However, to exploit these compelling nano-architectures as freestanding electrodes in electrochemical flow cells, e.g. water electrolysis, it is essential that the nanowire-network is accessible from all sides requiring a porous support structure. To demonstrate the advantage of the high volumetric NM surface area of 26 m 2 /cm 3 for water electrolysis up to 1 A/cm 2, we monolithically integrated a nickel NM with an open support grid in a facile and up-scalable fabrication flow. The freestanding NM electrodes show beyond state-of-the-art performance for the alkaline hydrogen- and oxygen evolution reaction (HER and OER), with over 100x enhanced current densities in respect to planar nickel. Interestingly, the regular nano-architecture of the electrodes causes an intrinsic catalytic effect for the HER. The high potential of these novel 4 μm thin electrodes toward high-throughput electrochemical applications is shown by the significant 400 mV lower overpotential compared to commercial 1.6 mm thick nickel foams (<0.01 m 2 /cm 3 ) in the alkaline anion-exchange membrane water electrolysis. Graphical abstract: Image 1 Highlights: Freestanding high surface area 26 m 2 /cm 3 nickel nanomesh electrodes for flow cells. Nanomesh electrodes reduce η compared to planar nickel (−285 mV HER,  −146 mV OER). Nanostructured electrode architecture shows intrinsic catalytic effect for HER. 4 μm nanomesh electrodes outperform 1.6 mm nickel foams in electrolyzer at 1 A/cm 2 .